Frequent mutations of genes encoding vacuolar H+‐ATPase components in granular cell tumors. Issue 6 (21st January 2019) - Sekimizu, Masaya; Yoshida, Akihiko; Mitani, Sachiyo; Asano, Naofumi; Hirata, Makoto; Kubo, Takashi; Yamazaki, Fumito; Sakamoto, Hiromi; Kato, Mamoru; Makise, Naohiro; Mori, Taisuke; Yamazaki, Naoya; et al.
Abstract: Granular cell tumors (GCTs) are rare mesenchymal tumors that exhibit a characteristic morphology and a finely granular cytoplasm. The genetic alterations responsible for GCT tumorigenesis had been unknown until recently, when loss‐of‐function mutations of ATP6AP1 and ATP6AP2 were described. Thus, we performed whole‐exome sequencing, RNA sequencing, and targeted sequencing of 51 GCT samples. From these genomic analyses, we identified mutations in genes encoding vacuolar H + ‐ATPase (V‐ATPase) components, including ATP6AP1 and ATP6AP2, in 33 (65%) GCTs. ATP6AP1 and ATP6AP2 mutations were found in 23 (45%) and 2 (4%) samples, respectively, and all were truncating or splice site mutations. In addition, seven other genes encoding V‐ATPase components were also mutated, and three mutations in ATP6V0C occurred on the same amino acid (isoleucine 136). These V‐ATPase component gene mutations were mutually exclusive, with one exception. These results suggest that V‐ATPase function is impaired in GCTs not only by loss‐of‐function mutations of ATP6AP1 and ATP6AP2 but also through mutations of other subunits. Our findings provide additional support for the hypothesis that V‐ATPase dysfunction promotes GCT tumorigenesis.